A dipole‐type millimeter‐wave antenna with directional radiation characteristics. Issue 3 (28th November 2019) - Dong, Yue; Li, Yingsong; Sim, Chow‐Yen‐Desmond; Xia, Yinfeng; Liu, Xiaoguang
Abstract: A dipole‐type millimeter‐wave (mm‐wave) antenna with directional radiation characteristics is presented. A radiating patch structure composed of a dipole‐type radiation patch and a rectangular‐shaped parasitic patch are initially investigated to achieve a wider bandwidth. To further improve the operating bandwidth and to realize a directional radiation characteristic, this radiating patch structure is top‐loaded above a conducting cavity‐backed ground structure, which has a low profile (thickness of 3 mm). The measured results show that the proposed mm‐wave antenna can achieve a wide 10‐dB bandwidth of 51.3% (29.6‐50.0 GHz) and stable gain across the desired frequency range. Furthermore, good directional characteristics over the entire mm‐wave frequency band with a compact antenna size of 0.64λ40GHz × 0.91λ40GHz × 0.43λ40GHz are also realized. Hence, it is suitable for many small size wireless mm‐wave systems.